Analysis of the Impact of the Ameroro Dam Development on the Welfare of Farmers in Konawe - Pradana, Dhika; Busnetty, Ida; Nurariyani, Dika (Jurnal Ilmiah Ilmu Administrasi Publik, 2025)
The Ameroro Dam in Konawe Regency, Southeast Sulawesi, was constructed to improve irrigation systems, control floods, and support agricultural productivity. This study uses qualitative content analysis based on secondary data including statistical reports, development planning documents, and environmental impact assessments from 2018–2023. The dam successfully provides irrigation for 3,363 hectares of farmland, leading to a 20% increase in rice productivity and a similar increase in farmers’ incomes. However, 375.86 hectares of forest were flooded, and 50 families were relocated, leading to socio-environmental challenges. While the dam enhances agricultural output and mitigates flood risks, issues such as loss of biodiversity and inadequate community involvement demand further policy attention. The Ameroro Dam policy yields positive agricultural and economic outcomes, but future development must integrate inclusive planning and ecological rehabilitation.